5 Rethinking reproductive politics in time, and time in UK reproductive politics: 1978‐2008. (April 2014) - Franklin, Sarah
Abstract : This paper explores two different but interlinked and contemporaneous debates over reproductive politics in which we can observe at least three distinct combinations of time. In the first part, I describe the shift in the 1980s to a 'biologized' time by British Christian Right‐to‐Life groups, who began to use a secularized ontogeny to promote and defend a religious definition of 'the way, the truth, and the life' – an altered 'theo‐ontology' based on the equivalence of the absolute value of human life, the truth (of biological life), and faith in Christ (as everlasting life). In the second part, I describe a differently 'remixed', and opposing, ontology (secular and semi‐secular, using a hybrid bio‐legal chronometry but orientated toward the timeless horizon of progress) that characterized the debate over the future of in vitro fertilization in the same period, leading up to the adoption of the first Human Fertilization and Embryology (HFE) Act in the UK in 1990. In the third part, I examine the legacy of these debates insofar as they are evident in the more recent political conflicts accompanying passage of an amended HFE Act in 2008 and the debate over so‐called 'cybrid embryos'. These episodes reveal how social movements 'are profoundly shaped by mediations and conflicts between diverse representations, technologies, social disciplines and rhythms of time'. I argue that the varied constructions of temporality in reproductive politics evident in these three distinct episodes are crucial to anthropological understandings of the meaning of 'biological control' in the context of stem cell research, cloning, tissue engineering, and reproductive biomedicine.